Preparation of Hybrid Chitosan/Silica Composites Via Ionotropic Gelation and Its Electrochemical Impedance Studies - Wonnie Ma, Iling Aema; Ammar, Sh.; Bashir, Shahid; Selvaraj, Manickam; Assiri, Mohammed Ali; Ramesh, Kasi; Ramesh, Subramaniam (Elsevier, 2020)
Hybrid materials are inimitable conjugates of organic/inorganic structures having synergetic behaviour and extraordinary properties. Therefore, hybrid chitosan/silica composite was synthesized by using sodium tripolyphosphate via ionotropic gelation technique. The obtained intercalation of hybrid chitosan/silica composite was characterized using Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) analysis. The surface morphology of the composite was studied through field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The EDX analysis was performed to find the wt.% of the present elements in the composite that showed the increment of O element up to 47.50 wt. % and the presence of Si (27.61 wt. %) revealed that the silica is present within the chitosan matrix, which demonstrates successful hybridization of chitosan/silica. Furthermore, the obtained hybrid chitosan/silica was incorporated within the epoxy matrix and electrochemical studies such as electrochemical impedance spectroscopy (EIS) was employed for 60 days. The experimental results revealed that the presence of hybrid chitosan/silica composite up to 0.8 wt. % resulted in a profound outcome as a considerable active reinforcing agent for corrosion prevention application with the highest coating resistance, (1.97 ± 0.01) × 1011 Ω and lowest breakpoint frequency, 51 × 10-3 Hz after 60 days. © 2020 Elsevier B.V.